Natural tyrosinase enzyme inhibitors: A path from melanin to melanoma and its reported pharmacological activities - Suresh Mohankumar (Biochimica et Biophysica Acta (BBA) - Reviews on Cancer, 2023)
The skin containing melanin pigment acts as a protective barrier and counteracts the UVR and other environmental stressors to maintain or restore disrupted cutaneous homeostasis. The production of melanin pigment is dependent on tyrosine levels. L-tyrosine and L-dihydroxyphenylalanine (L-DOPA) can serve both as a substrates and intermediates of melanin synthetic pathway and as inducers and positive regulators of melanogenesis. The biosynthesis of melanin is stimulated upon exposure to UVR, which can also stimulate local production of hormonal factors, which can stimulate melanoma development by altering the chemical properties of eu- and pheomelanin. The process of melanogenesis can be altered by several pathways. One involves activation of POMC, with the production of POMC peptides including MSH and ACTH, which increase intracellular cAMP levels, which activates the MITF, and helps to stimulate tyrosinase (TYR) expression and activity. Defects in OCA1 to 4 affects melanogenic activity via posttranslational modifications resulting in proteasomal degradation and reducing pigmentation. Further, altering, the MITF factor, helps to regulate the expression of MRGE in melanoma, and helps to increase the TYR glycosylation in ER. CRH stimulates POMC peptides that regulate melanogenesis and also by itself can stimulate melanogenesis. The POMC, P53, ACTH, MSH, MC1R, MITF, and 6-BH4 are found to be important regulators for pigmentation. Melanogenesis can affect melanoma behaviour and inhibit immune responses. Therefore, we reviewed natural products that would alter melanin production. Our special focus was on targeting melanin synthesis and TYR enzyme activity to inhibit melanogenesis as an adjuvant therapy of melanotic melanoma. Furthermore, this review also outlines the current updated pharmacological studies targeting the TYR enzyme from natural sources and its consequential effects on melanin production.